PENGARUH PEMBERIAN REBUSAN DAUN LABU KUNING TERHADAP PRODUKSI ASI PADA IBU MENYUSUI - Visti Delvina, Tiara Wulandary (Universitas Fort de Kock Bukittinggi, 2022)
Common problems that are often experienced by breastfeeding mothers are problems with the smooth production of breast milk. This can be influenced by nutritional factors during pregnancy and breastfeeding their babies. Because the food that is not consumed by the mother will have an impact on the baby's food intake and have an impact on the growth and development of the baby. This type of research was a quasi-experimental design with one group pretest-posttest and the data were analyzed by univariate and bivariate analysis. The research was conducted in December 2021 by way of treatment. The population in this study were all breastfeeding mothers who were breastfeeding from infants 0-3 weeks in the HiangCommunity Health Center, Kerinci Regency. The sampling technique was purposive sampling by determining 10 respondents who were given pumpkin vegetables.Based on the results of the study, it was known that the average milk production for breastfeeding mothers before giving was 6.90. The average milk production in breastfeeding mothers after giving was 10.00. In conclusion, it was known that the p-value was 0.000 so it was known that there was an effect of consumption of boiled pumpkin leaves on breast milk production in the working area of the HiangCommunity Health Center, Kerinci Regency in 2022. Based on the research, it is expected that breastfeeding mothers should consume more foods that can stimulate milk production, such aspumpkin leaves 200 grams per day and get used to consuming it. And it is hoped that Hiang Community Health Center officers can socialize so that breastfeeding mothers who are constrained by breast milk can consume boiled pumpkin leaves. Keywords : Pumpkin Leaf Consumption, Breast Milk Production, Breastfeeding Mothers